The Evolution of Low Mass Contact Binaries - Stępień, Kazimierz; Gazeas, Kosmas (From Interacting Binaries to Exoplanets: Essential Modeling Tools, 2012)
We discuss the origin and evolution of low mass contact binaries with Porb shorter than 0.3 d that have properties somewhat different from the rest of the contact binaries. A comparison of an evolutionary model set with observations shows that both components are on the main sequence, the age of the binaries is at least several Gyr, while the contact phase lasts only less than 1 Gyr.
Keywords: contact binaries; stellar evolution; W UMa stars